Case Study On AirAsia Berhad - Ungoh, Sunyong (2007)
This case study is divided into two parts, which are case writing and case analysis. Case writing discussed about general information on AirAsia such as its strategies, operation, challenges its face and financial information. This section also looks into low cost carrier development in Asia.